MPLEMENTASI MODEL PROBLEM BASED LEARNING (PBL) BERBANTUAN KAHOOT DALAM MENINGKATKAN HASIL BELAJAR DASAR TEKNOLOGI OTOMOTIF PADA PESERTA DIDIK KELAS X TKR DI SMKN 1 KOTA PADANG - Wira Buana, Muhammad; Wagino, W; Sugiarto, Toto; Rifdarmon (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low learning outcomes of students in the DTO subject in the 10th-grade TKR class at SMKN 1 Padang. This is due to a suboptimal learning process, particularly regarding student engagement, the use of learning models that lack variety, and the minimal use of interactive media. These conditions have resulted in a lack of active student participatiob in the learning processs. Therefore, the implementation of a more innovative learning model is nedded to improve student learning outcomes. This study aims to improve student learning outcomes in the DTO subject through the implementation of a Kahoot-assisted Problem Based Learning (PBL) model. The research design used was Classroom Action Research (CAR), conducted in two cycles, comprising the stages of planning, implementation, observation, and reflection. The research subjects consisted of 10th-grade TKR studens at SMKN 1 Kota Padang, the teacher as an observer, and the researcher as the action implementer. Dara were collected through observation and documentation techniques, the analyzed using descriptive qualitative and quantitative methods. The research results indicate improvements in every aspect. The quality of the teaching modules improved from 76,24 (C) in Cycle I to 95,33 (SB) in Cyle II. Thecher and student engagement increased from 71,69 (C) to 90,50 (B). Student learning outcomes also improved in the areas of attiude, knowledge, and skills, moving from the “adequate” category in Cycle I to “good” in Cycle II. Thus, it can be concluded that the implementation of the Kahoot-assisted Problem-Based Learning model is effective in improving student learning outcomes in the DTO subject.